Implementation Of The Stunting Prevention Socialization Program And Provision Of PMT In Gunjan Asri Village - Mastini, Luh; Wardani, Rizkika Ari; Pareza, Zian; Husna, Nadiatul; Mulyono, Ana (Abdi Masyarakat, 2025)
Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia, including at the local level. This study aims to describe the implementation of stunting prevention and management programs in Gunjan Asri Village, North Lombok Regency, focusing on stunting prevention awareness campaigns and the provision of supplementary feeding (PMT). This research employed a descriptive qualitative method with data collected through observation, interviews, and documentation involving posyandu cadres, village officials, health center staff, and parents of children under five. The findings show that the awareness campaign conducted on August 30, 2025, successfully improved community understanding of the importance of balanced nutrition, parenting practices, and child health, although its effectiveness still requires repeated activities to sustainably change behavior. Meanwhile, the supplementary feeding program held on September 6, 2025, contributed positively to improving children’s nutritional intake, particularly for six children identified as stunted, but its implementation was constrained by limited funding, resulting in a one-time activity. These findings highlight that awareness campaigns and supplementary feeding can serve as effective strategies in supporting the acceleration of stunting reduction, but greater consistency, budget support, and cross-sector collaboration are required to ensure optimal and sustainable impact.